1992
DOI: 10.1111/j.1476-5381.1992.tb14467.x
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide‐sensitivity of the adenosine 5′‐triphosphate‐dependent K+ channel in mouse pancreatic β‐cells

Abstract: 1. In mouse pancreatic P-cells the regulation of the diazoxide-sensitivity of the adenosine 5'-triphosphate-dependent K+ channel (K-ATP-channel) was 5. Diazoxide (50 or 300 jM) prevented the complete channel block induced by saturating tolbutamide concentrations in the presence of Mg2" and ADP (1 mM). 6. In the presence of Mg2", the K-ATP-channel-blocking potency of cytosolic ATP decreased in the order inside-out> outside-out> whole-cell configuration of the patch-clamp technique. 7. It is concluded that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 33 publications
(64 reference statements)
4
40
1
Order By: Relevance
“…It has also been suggested that GTP is partially degraded into GDP by membrane patches (41). Degradation of ATP into ADP by membrane patches has been demonstrated directly (43,44). Finally, and most importantly, GDP, like ADP, opens K ϩ -ATP channels in the presence of ATP, whereas GTP is ineffective under these conditions (40,42,45).…”
Section: Discussionmentioning
confidence: 96%
“…It has also been suggested that GTP is partially degraded into GDP by membrane patches (41). Degradation of ATP into ADP by membrane patches has been demonstrated directly (43,44). Finally, and most importantly, GDP, like ADP, opens K ϩ -ATP channels in the presence of ATP, whereas GTP is ineffective under these conditions (40,42,45).…”
Section: Discussionmentioning
confidence: 96%
“…Stimulation of insulin secretion requires reduction of the P O of pancreatic ␤-cell K ATP channels to values Ͻ0.02 (12). Both increased spontaneous P O values (Fig.…”
mentioning
confidence: 95%
“…Consistent with the idea that nucleotide-induced channel inhibition results from interaction with the interburst closed states (39,40), E23K decreased sensitivity toward inhibitory ATP 4Ϫ in the models for the heterozygous and homozygous genotypes (K/K, with K in position 23 of K IR 6.2 in both alleles). Stimulation of insulin secretion requires reduction of the P O of pancreatic ␤-cell K ATP channels to values Ͻ0.02 (25,41). Both the increased spontaneous P O values and the reduced ATP sensitivity contributed to a rightward shift of the corresponding ATP concentration (IC R2 value) through E23K (38).…”
Section: Effect Of E23k a Common Polymorphism In K Ir 62 On Nucleomentioning
confidence: 99%